Estimation of stability derivatives in pitch for an oscillating 2-D wedge in supersonic Flow - Pavithra, Shanbhag,; Bashir, Musavir; S, Lavanya; Khan, Sher Afghan (Pushpa Publishing House, Allahabad, India, 2016)
A similitude has been obtained for a pitching oscillating two dimensional wedge with attached bow shock at high angle of incidence in supersonic flow. A strip theory given by Ghosh [1] for flow in spanwise location has been used. For the two-dimensional flow, a normal shock is formed directly in front of the body and becomes a curved oblique shock as it extends around the body. This integrates with the similitude model leading to one-dimensional piston theory reformulated by Ghosh [1] from initial works of Lighthill [2] and Miles [3]. Therefore, precise form of simple relations for damping and stiffness derivatives in pitch has been obtained. The present theory is valid only for shock wave which is attached with the nose of the wedge. From the combination of theory developed, we can evaluate the derivatives for stiffness and damping in pitch for a wide range of supersonic Mach numbers, for various pivot positions, and angle of incidence. Substantially the same results are being validated with the analytical results of Liu and Hui [4] with great simplicity.